Cross-sectional study on the association between 24-hour urinary potassium excretion and the risk of H-type hypertension and non-H-type hypertension in Chinese adults - He, Qingfang; Du, Xiaofu; Chen, Xiangyu; Wang, Lixin; Fang, Yujia; Zhong, Jieming (Frontiers in Endocrinology, 2025)
ObjectiveReports on urinary potassium excretion and H-type hypertension remains rare. We aimed to describe the relationship between 24-hour (h) urinary potassium excretion and the risk of H-type hypertension and non-H-type hypertension, thus to guide personal and public health campaigns including dietary recommendations to lower H-type hypertension and non-H-type hypertension in China.MethodsIn 2020 in Zhejiang, China, a cross-sectional survey on Salt Reduction and Prevention of Hypertension was conducted by using a stratified multistage random sampling strategy, with participants aged 21 to 72 years. Standardized questionnaires, physical examinations and laboratory measurements were carried out among them, as well as survey on knowledge, attitudes, and behavior (KAB) correlated with salt and hypertension. 24-h urine specimens were collected for sodium and potassium excretion measurement. Subjects were divided into three groups, normal blood pressure, non-H-type hypertension and H-type hypertension, according to their blood pressure, self-reported history of hypertension and blood homocysteine (Hcy) levels.Results1141 participants with complete information were obtained with the median age of 53 years, 46.0% were males, 41.7% were hypertension, among which 80.5% were H-type hypertension. The median Hcy and 24-h urinary potassium were 11.7μmol/L and 40.83 mmol/24h, respectively. After controlling for confounding factors, logistic regression analysis displayed that for every 1 mmol/L increase in 24-h urinary potassium excretion, the risk of H-type hypertension and non-H-type hypertension decreased by 1.4% (OR=0.986, 95% CI: 0.978-0.995, P=0.002) and 1.7% (OR=0.983, 95% CI: 0.968-0.998, P=0.025), respectively. Restricted cubic spline (RCS) curves showed that with the increase of 24-h urinary potassium excretion, the risk of both H-type hypertension (P= 0.008) and non-H-type hypertension (P=0.027) decreased, while there were no nonlinear dose-response relationships between 24-h urinary potassium excretion with both H-type hypertension (P for non-linearity = 0.881) and non-H-type hypertension (P for non-linearity = 0.101). Participants’ level of KAB in H-type hypertension group presented a lower percentage (86.2%) knowledge of the risk factors of hypertension, a highest percentage (12.5%) of self-assessment of excessive salt intake, but a lowest percentage (23.0%) of taking initiative to reduce salt intake.Conclusion24-h urinary potassium excretion was negatively associated with the risk of both H-type hypertension and non-H-type hypertension, with a more stable negative response observed in H-type hypertension across logistic models and RCS curves. It is recommended that hypertension particularly H-type hypertension patients strengthen their KAB regarding salt reduction and hypertension, adopt reasonable dietary patterns, to improve potassium intake, and ultimately aid in better Hcy and blood pressure management.